Genetic variability in egg production-associated microsatellites in Rhode Island Red chicken - DEBNATH, JOWEL; KUMAR, SANJEEV; RAHIM, ABDUL; YADAV, RAMJI (The Indian Journal of Animal Sciences, 2017)
Present investigation was carried out in 114 birds belonging to selected strains of Rhode Island Red chicken maintained at institute experimental layer farm with the objective to analyze polymorphism in egg production associated microsatellite loci and to determine various population genetics statistics based on allelic polymorphism. Genomic DNA samples were isolated from all experimental birds and PCR was performed using primers for ten microsatellite loci, reported to be associated with egg production traits in chicken. Alleles were separated on 3.4% MetaPhoreTM agarose and their sizes were determined by Quantity One software. Allelic data were analyzed by POPGENE. Allele numbers varied from 2 to 5 and average number of alleles per locus was 4.00±0.37 (Na). Allele sizes ranged from 99-280 bp. Allele frequency per locus ranged from 0.0225-0.8919. Nei’s heterozygosity, Botstein’s polymorphic information content (PIC) and Wright’s fixation indices at each locus were estimated. All studied microsatellite loci were polymorphic and estimated PIC ranged from 0.19 (ADL0273) to 0.72 (MCW0110). Seven loci were moderate to highly polymorphic (PIC>0.50). Nei’s heterozygosity per locus ranged from 0.20 (ADL0273) to 0.77 (MCW0110). Averaged effective number of alleles (Ne), Shannon’s Information index (I) and Wright’s fixation indices were 2.71±0.26, 1.0654±0.1046 and 0.5126±0.0757, respectively. Average observed (Ho) and expected (He) heterozygosities were 0.3036±0.0625 and 0.5930±0.0505, respectively. Study revealed prevalence of heterozygosity as the Ne was lesser than the Na. It further revealed that the population was under Hardy-Weinberg disequilibrium as (He) was more than (Ho).Chi square and G-square estimates were significant, which suggested that the studied microsatellite loci might have some association with ongoing selection for 40-week part-period egg production in RIR chicken.